Allosteric Modulation of Muscarinic Acetylcholine Receptors - Gregory, Karen J.; Sexton, Patrick M.; Christopoulos, Arthur (Current Neuropharmacology, 2007)
Muscarinic acetylcholine receptors (mAChRs) are prototypical Family A G protein coupled-receptors. The five mAChR subtypes are widespread throughout the periphery and the central nervous system and, accordingly, are widely involved in a variety of both physiological and pathophysiological processes. There currently remains an unmet need for better therapeutic agents that can selectively target a given mAChR subtype to the relative exclusion of others. The main reason for the lack of such selective mAChR ligands is the high sequence homology within the acetylcholine-binding site (orthosteric site) across all mAChRs. However, the mAChRs possess at least one, and likely two, extracellular allosteric binding sites that can recognize small molecule allosteric modulators to regulate the binding and function of orthosteric ligands. Extensive studies of prototypical mAChR modulators, such as gallamine and alcuronium, have provided strong pharmacological evidence, and associated structure-activity relationships (SAR), for a “common” allosteric site on all five mAChRs. These studies are also supported by mutagenesis experiments implicating the second extracellular loop and the interface between the third extracellular loop and the top of transmembrane domain 7 as contributing to the common allosteric site. Other studies are also delineating the pharmacology of a second allosteric site, recognized by compounds such as staurosporine. In addition, allosteric agonists, such as McN-A-343, AC-42 and N-desmethylclozapine, have also been identified. Current challenges to the field include the ability to effectively detect and validate allosteric mechanisms, and to quantify allosteric effects on binding affinity and signaling efficacy to inform allosteric modulator SAR.
Keywords: structure-activity studies